Methylparaben induces malformations and alterations on apoptosis, oxidant–antioxidant status, ccnd1 and myca expressions in zebrafish embryos - ALTURFAN, EBRU IŞIK (My University, 2019)
Methylparabens (MP) are widely used as preservatives in cosmetics, pharmacy, and food industry. Although acute toxicity studies in animals indicated that parabens are not significantly toxic, the effects of chronic exposure under sublethal doses are still unknown and the number of related studies is limited. Our aim was to evaluate the effects of MP on the development of zebrafish embryos focusing on development, locomotor activity, oxidant–antioxidant status, apoptosis, and ccnd1 andmyca expressions. The expressions of ccnd1 andmycawere determined by RT-PCR. Lipid peroxidation (LPO), nitric oxide (NO), and glutathione-S-transferase (GST) activities were determined spectrophotometrically. Apoptosis was determined using acridine orange staining. Locomotor activity was measured using touch-evoked movement test. MP exposure increased malformations, LPO, apoptosis, ccnd1 and myca expressions, and decreased GST activities and NO levels compared with the control group. Our findings will lead to further understanding of the mechanism of MP toxicity, and merit further research.
Keywords: Temel Bilimler; Natural Sciences; Temel Bilimler (SCI); Doğa Bilimleri Genel; ÇOK DİSİPLİNLİ BİLİMLER; Natural Sciences (SCI); NATURAL SCIENCES, GENERAL; MULTIDISCIPLINARY SCIENCES; Multidisciplinary; apoptosis; ccnd1; methylparaben; myca; oxidant–antioxidant status